The Bible's most fascinating people : an illustrated collection : stories from the Old and New Testament - Nettelhorst, R. P. (New York : Reader's Digest, 2008)
Features important figures and their stories from the Old and New Testaments in a chronologically arranged volume that includes detailed family trees, historical information, and illustrations of classical works of art.
Keywords: Bible -- Biography; Bible stories, English